Estimates of groups of deviations of faber sums and strong summability of faber series on classes of ψ-integrals - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We establish upper bounds for a group of ϕ*-deviations of Faber sums on the classes of ψ-integrals in a complex plane introduced by Stepanets.